Preliminary crystallographic analysis of the major capsid protein P2 of the lipid-containing bacteriophage PM2. - Abrescia, N; Kivelä, H; Grimes, J; Bamford, J; Bamford, D; Stuart, D (2005)
PM2 (Corticoviridae) is a dsDNA bacteriophage which contains a lipid membrane beneath its icosahedral capsid. In this respect it resembles bacteriophage PRD1 (Tectiviridae), although it is not known whether the similarity extends to the detailed molecular architecture of the virus, for instance the fold of the major coat protein P2. Structural analysis of PM2 has been initiated and virus-derived P2 has been crystallized by sitting-nanodrop vapour diffusion. Crystals of P2 have been obtained in space group P2(1)2(1)2, with two trimers in the asymmetric unit and unit-cell parameters a = 171.1, b = 78.7, c = 130.1 A. The crystals diffract to 4 A resolution at the ESRF BM14 beamline (Grenoble, France) and the orientation of the non-crystallographic threefold axes, the spatial relationship between the two trimers and the packing of the trimers within the unit cell have been determined. The trimers form tightly packed layers consistent with the crystal morphology, possibly recapitulating aspects of the arrangement of subunits in the virus.